An outbreak of norovirus gastroenteritis associated with asymptomatic food handlers in Kinmen, Taiwan - Meng-Yu Chen; Wan-Chin Chen; Pei-Chen Chen; Shan-Wei Hsu; Yi-Chun Lo (BMC Public Health, 2016)
Abstract Background In February 2015 an outbreak of gastroenteritis occurred in a distillery in Kinmen, Taiwan. At least 450 affected employees developed the symptoms of diarrhea and vomiting after attending a lunch banquet on 6 February. Epidemiological, laboratory and environmental investigations were conducted to identify the agent and source of this outbreak. Methods A case–control study was carried out among lunch attendees from the distillery. Using a semi-structured questionnaire, food and beverage consumption in the lunch banquet was assessed, as well as demographic and clinical data of the exposed people. An outbreak case was defined as a diner who developed at least three following symptoms: diarrhea, vomiting, abdominal pain, nausea, chills and/or weakness in the 72 h following the lunch. Controls were defined as lunch attendees who did not have any of the above symptoms. Rectal swabs or stool samples of the symptomatic exposed diners and food handlers as well as food and environmental samples were collected to test potential bacteria and viruses. Norovirus was detected by reverse transcription-polymerase chain reaction and sequence analysis. An environmental assessment, including environmental inspection of the restaurant and a review of work practices of food workers, was undertaken. Results Of 363 respondents with complete data, 169 met the case definition and 111 met the control definition. Consumption of pork liver in cold appetizers (adjusted odd ratio (aOR) 3.23; 95 % confidence interval (CI): 1.26–8.30) and lamb chops (aOR: 3.98, 95 % CI: 1.74–9.11) were each associated with increased risk of illness. No cases but two asymptomatic food handlers who prepared or cooked the implicated foods tested positive for norovirus genotype I.6. Food and environmental samples were negative for any bacteria. Environmental assessment indicated that hand washing facilities were not properly accessible to food handlers. Inappropriate hygiene practices in food handlers may have contributed to food contamination. Conclusion Our investigation suggests that etiological agent of this outbreak was norovirus. The food vehicles were pork liver and lamb chops, which may have been contaminated by asymptomatic infected food handlers. Strict adherence to hand hygiene practices and access to hand washing facilities should be reinforced to prevent such foodborne outbreaks.